2018
DOI: 10.1038/s41380-018-0027-3
|View full text |Cite
|
Sign up to set email alerts
|

CNTNAP2 stabilizes interneuron dendritic arbors through CASK

Abstract: Contactin associated protein-like 2 (CNTNAP2) has emerged as a prominent susceptibility gene implicated in multiple complex neurodevelopmental disorders, including autism spectrum disorders (ASD), intellectual disability (ID), and schizophrenia (SCZ). The presence of seizure comorbidity in many of these cases, as well as inhibitory neuron dysfunction in Cntnap2 knockout (KO) mice, suggests CNTNAP2 may be crucial for proper inhibitory network function. However, underlying cellular mechanisms are unclear. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 74 publications
3
60
0
Order By: Relevance
“…GluA1 (synaptic membrane protein) was highly enriched in the crude membrane (S5), and synaptic (S6) fractions while PSD95 (synaptic cytosolic protein) was only enriched in the S6 fraction; β‐tubulin (nonsynaptic cytosolic protein) was absent from either S5 or S6 fractions (Figure b, bottom). We found both PAR3 and CNTNAP2 in the S6 (synaptic) fraction, consistent with previous publications (Chen et al, ; Gao et al, ; Lin et al, ; Oiso et al, ). We also validated previous studies and showed strong colocalization of PAR3 with PSD95 (Figure S1).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…GluA1 (synaptic membrane protein) was highly enriched in the crude membrane (S5), and synaptic (S6) fractions while PSD95 (synaptic cytosolic protein) was only enriched in the S6 fraction; β‐tubulin (nonsynaptic cytosolic protein) was absent from either S5 or S6 fractions (Figure b, bottom). We found both PAR3 and CNTNAP2 in the S6 (synaptic) fraction, consistent with previous publications (Chen et al, ; Gao et al, ; Lin et al, ; Oiso et al, ). We also validated previous studies and showed strong colocalization of PAR3 with PSD95 (Figure S1).…”
Section: Resultssupporting
confidence: 93%
“…We performed a yeast two‐hybrid screen of a mouse brain cDNA library with the entire CNTNAP2 intracellular domain (ICD) as bait (amino acids 1284–1331) to find intracellular interactors of CNTNAP2 (Figure a). Out of three million candidates screened, we identified 41 unique clones (Gao et al, ), with PAR3 being one of the most intriguing, given its role as a spatial organizer (Ahmed & Macara, ; Duman et al, ; Zhang & Macara, ). We confirmed this positive result by demonstrating yeast growth on high stringency plates only when expressing both bait/prey plasmids, indicating a direct physical interaction (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CNTNAP2 is highly expressed in the frontal and temporal lobes of the developing human brain, and the striatal circuits and frontal cortex of the adult brain. Functional studies indicated that CNTNAP2 was involved in dendrite stabilization, neuron migration, subsequent laminar organization, and connectivity of specific neural circuits [Gao et al, ; Poliak et al, ; Strauss et al, ; Zerbi et al, ]. Cntnap2 knockout neurons showed impaired axonal growth and synaptic abnormalities, which might play important roles in autism [Canali et al, ; Spooren, Lindemann, Ghosh, & Santarelli, ; Varea et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Probably CNVs and SNVs of the HNRNPU gene may produce distinct phenotypic outcomes. In view of the plethora of possibly pathogenic molecular mechanisms, there is a clear need for in vitro and in vivo functional studies to assess the effects of CNVs and the different SNVs in HNRNPU, as has been done for CNTNAP2 SNVs [Brumback et al, 2017;Scott et al, 2017;Canali et al 2018;Gao et al, 2018;Liska et al, 2018;Vogt et al, 2018;Zerbi et al, 2018]. The outcome of such studies may help us understand the phenotypic variability in patients with CNVs and SNVs affecting HNRNPU .…”
mentioning
confidence: 99%